ANALISIS KANDUNGAN MERKURI (Hg) PADA KRIM PAGI DAN KRIM MALAM DI KLINIK KECANTIKAN YOGYAKARTA - Puteri Puspitasyar; Eva Runi Khristiani; Novita Sekarwati (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACTMercury is a toxic metal that, even in low concentrations, can impair fertility, suppress the immune system, kidney damage, nerve damage, and disrupt the workings of the brain. In accordance Annex I to Regulation Head POM No. HK.00.05.42.1018 of 2008 on Cosmetic Ingredients, stated that Mercury and its compounds are included in the list are prohibited except Cosmetic Mercury in the compound as listed in Annex IV List of permitted preservatives Used In Cosmetics, phenyl mercury salts and thiomersal (NN) with The maximum level of 0.007% (calculated as Hg).The purpose of the work of writing Scientiﬁ c is determine the content of mercury (Hg) and to compare in the cream morning and night cream in Yogyakarta Beauty Clinic. This type of research is to use the method of Reaction Colour / MA PPOMN 53 / K0 / 13, that the results will be analyzed descriptively. Based on the results of 8 samples taken in cosmetic beauty clinic A, B, C, and D in the area of Yogyakarta, the sample consist of 4 cream morning and 4 nigh the result is saturation of mercury (Hg)but still less than 0,007 ppm and this is safe to use.